Bittersweet! Understanding and Managing Electronic Word of Mouth. Issue 2 (21st June 2013) - Kietzmann, Jan; Canhoto, Ana; Plangger, Kirk; Mills, Adam J.
<x xml:space="preserve">Abstract</x> For 'viral marketing', it is critical to understand what motivates consumers to share their consumption experiences through 'electronic word of mouth' (eWoM) across various social media platforms. This conceptual paper discusses eWoM as a coping response dependent on positive, neutral, or negative experiences made by potential, actual, or former consumers of products, services, and brands. We combine existing lenses and propose an integrative model for unpacking eWoM to examine how different consumption experiences motivate consumers to share eWoM online. The paper further presents an eWoM Attentionscape as an appropriate tool for examining the amount of attention the resulting different types of eWoM receive from brand managers. We discuss how eWoM priorities can differ between public affairs professionals and consumers, and what the implications are for the management of eWoM in the context of public affairs and viral marketing. Copyright © 2013 John Wiley & Sons, Ltd.